Enhancing skill transfer in tennis using representative learning design - Krause, L.; Farrow, D.; Pinder, R.; Buszard, T.; Kovalchik, S.; Reid, M. (Journal of Sports Sciences, 2019)
Representative Learning Design advocates that practice should simulate the demands of competition. The effectiveness of increased task representativeness to improve serving skill of junior tennis players was assessed after a six-week intervention. Thirty-three participants (15.4 ± 1.9 years of age) were assigned to one of the three groups; "serve only" (participants served to no opponent), "serve return" (participants served to an opponent and hit no extra shots) or "serve +3rd" (participants served to an opponent and hit one extra shot). Using the validated representative practice assessment tool (RPAT) tasks were considered to be low, moderate and high in task representativeness, respectively. Participants hit 56 serves, twice weekly for 6-weeks. Pre and post serving performances were assessed via a skill test and in-situ matchplay using SportsCode and HawkEye ball tracking, respectively. Serve speed, landing locations, serve angle and positional advantage was obtained for 1st and 2nd serves. The relationship between increasing representativeness and increased skill acquisition was not linear, rather different behaviours emerged. For example, when hitting 2nd serves in matchplay, the low and moderate representative groups prioritised speed over placement while the high representative group prioritised placement over speed. Coaches therefore need to carefully individualise representativeness to an athletes` specific needs.